Implementation of a Web-Based Learning Management System to Support Parental Involvement in Digital Learning - Abdul Adam Abdullah; Ni Putu Yulia; Aeriyn Ahmad (Jurnal Abdimas Cendekiawan Indonesia, 2026)
Parental involvement in the learning process is a crucial factor in supporting student academic success in the digital education era. However, limited academic monitoring systems in schools often result in suboptimal communication between teachers and parents. This community service activity aims to implement a web-based Learning Management System (LMS) with monitoring features to support parents in digital learning. The program, implemented at Epsom College in Malaysia, encompasses needs analysis, system design, LMS implementation, user training, mentoring, and system evaluation. The system was developed using the Dynamic Systems Development Method (DSDM) approach, while testing was conducted using Black Box Testing and questionnaire-based quantitative evaluation. Participants included 15 teachers, 48 ​​students, and 32 parents. The implementation results showed that the system helped teachers manage digital learning, facilitated student access to materials and assignments, and increased parental involvement in monitoring students' academic progress in real time. User evaluation results showed a system feasibility rating of 86.2%, categorized as very feasible. User response analysis also showed a 31.4% increase in academic communication effectiveness after system implementation. These findings suggest that web-based LMS can support digital learning transformation while strengthening collaboration between schools and families.